Electronic dictionaries in educational process in higher education - Euphym G. Vyshkin; Natalia N. Nemich; Anna A. Khokhlova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper considers an application of electronic dictionaries in the educational process as a promising method adapting modern education to the increasing information flow. The possibilities of using electronic dictionaries prove them to be a source of high-quality reference material and useful and necessary modern tool in foreign language learning. The paper points out the functionality of electronic dictionaries, their advantages and disadvantages. The opportunities of electronic dictionaries are wide enough: speed, convenience in finding information, large volume, sound and graphic illustration of the word, spell checker, interactivity, text conciseness, etc. Electronic dictionaries are based on modern lexical material, reflecting the language and speech tendencies, making the translation process fast and interactive, thus becoming a universal tool in the educational process of higher education. The authors point out that students have the opportunity to use the digital resource during lectures, practical studies and independent work.